1990
DOI: 10.1142/9789812798336_0003
|View full text |Cite
|
Sign up to set email alerts
|

Partition Function of the Eight-Vertex Lattice Model

Abstract: The partition function of the zero-field``Eight-Vertex'' model on a square M by N lattice is calculated exactly in the limit of M, N large. This model includes the dimer, ice and zerofield Ising, F and KDP models as special cases. In general the free energy has a branch point singularity at a phase transition, with an irrational exponent. Academic Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
131
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(135 citation statements)
references
References 0 publications
1
131
0
3
Order By: Relevance
“…On this level the operatorsŘ (1) andŘ (2) corresponding to these permutations are the elementary building blocks but the R-matrix is a composite object.…”
Section: 2)mentioning
confidence: 99%
See 3 more Smart Citations
“…On this level the operatorsŘ (1) andŘ (2) corresponding to these permutations are the elementary building blocks but the R-matrix is a composite object.…”
Section: 2)mentioning
confidence: 99%
“…On this level the operators S i , i = 1, 2, 3 are elementary building blocks. Now the operatorsŘ (1) ,Ř (2) and R-matrix are composite objects. So we have the chain of inclusions with increasing symmetry…”
Section: 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…These results all rely on the technique of functional relations [17] about the transfer matrix and fusion matrices of the associated τ (2) -model in the extended study of chiral Potts model as a descendent of the six-vertex model found in [19]. The study is along the line of T Q-relation method invented by Baxter in solving the eigenvalue problem of the eight-vertex model [5,6,7]. The Q-matrix of the τ (2) -model considered is the chiral Potts transfer matrix.…”
Section: Introductionmentioning
confidence: 99%